2009
DOI: 10.1002/jmv.21535
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Chinese measles vaccines by analysis of complete genomic sequences

Abstract: The complete genomic sequences of two Chinese measles vaccine viruses, Shanghai-191 (S-191) and Changchun-47 (C-47), were determined and compared to the sequences of other measles vaccine strains as well as the prototype measles strain, Edmonston wild-type (Edwt). Compared to Edwt, S-191 and C-47 had 49 and 43 nucleotide changes, respectively. These differences were found at 52 nucleotide positions that were not found in other vaccine strains. Phylogenetic analysis of the all of the available genomic sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Virus isolation was conducted by provincial laboratories and isolates were transported to the NLM in Beijing for molecular characterization. In this study, with the exception of one genotype A strain from Shandong province identified as a vaccine reaction, all strains were members of cluster 1 of genotype H1 and no cluster 2 [11] of H1 genotype were detected in 2006-2007 (Figure 3,4, 5). The results of the phylogenetic analysis from nucleotide positions 1230 to 1685 of the sequences of N gene are shown in Figures 3, 4 and 5.…”
Section: Resultsmentioning
confidence: 58%
“…Virus isolation was conducted by provincial laboratories and isolates were transported to the NLM in Beijing for molecular characterization. In this study, with the exception of one genotype A strain from Shandong province identified as a vaccine reaction, all strains were members of cluster 1 of genotype H1 and no cluster 2 [11] of H1 genotype were detected in 2006-2007 (Figure 3,4, 5). The results of the phylogenetic analysis from nucleotide positions 1230 to 1685 of the sequences of N gene are shown in Figures 3, 4 and 5.…”
Section: Resultsmentioning
confidence: 58%
“…The remaining strains were also likely to be related to vaccination because of their identical sequences. There were two slightly different Shanghai-191 N gene sequences (two nucleotide difference) available on GenBank and both were included in the phylogenetic analysis [Rota et al, 1994;Xu et al, 2004;Zhang et al, 2009c]. If more than one strain shared the same sequence, only one representative strain from each year was selected for phylogenetic analysis.…”
Section: Genotypingmentioning
confidence: 99%
“…Apart from subtype H1a, subtypes H1b and H1c were also detected in China until 2006 [Zhang et al, , 2009c. It was reported that subtype H1a has replaced subtypes H1b and H1c to become the predominant circulating strain in China since 2000 [Zhang et al, 2009a].…”
mentioning
confidence: 98%
“…In this study, we identified and characterized an IFN-inducing DI RNA of the copy-back type from MV vaccine strain Hu-191. With 50 nucleotide substitutions, the Hu-191 virus is more divergent from the Edmonston strain than most other vaccine strains (41). It has not previously been documented whether the Hu-191 virus produces DI RNA like other vaccine strains, such as strains Zagreb, AIK-C, and CAM-70 (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…To verify this, we first examined the induction of IFNs and cytokines by a vaccine strain of MV named Hu-191. The Hu-191 vaccine was developed in Shanghai, China, using a locally isolated strain and has been the most extensively used MV vaccine in the Chinese vaccination program (40,41). In fact, it has been used for measles immunization in all provinces in China since 2003.…”
Section: Induction Of Ifn-␤ and Cytokines By MV Vaccine Strainmentioning
confidence: 99%